Impact of performance grading on annual numbers of acute myocardial infarction-associated emergency department visits in Taiwan: Results of segmented regression analysis. Issue 42 (October 2016) - Tzeng, I-Shiang; Liu, Su-Hsun; Chen, Kuan-Fu; Wu, Chin-Chieh; Chen, Jih-Chang
Abstract : Abstract: To reduce patient boarding time at the emergency department (ED) and to improve the overall quality of the emergent care system in Taiwan, the Minister of Health and Welfare of Taiwan (MOHW) piloted the Grading Responsible Hospitals for Acute Care (GRHAC) audit program in 2007–2009. The aim of the study was to evaluate the impact of the GRHAC audit program on the identification and management of acute myocardial infarction (AMI)-associated ED visits by describing and comparing the incidence of AMI-associated ED visits before (2003–2007), during (2007–2009), and after (2009–2012) the initial audit program implementation. Using aggregated data from the MOHW of Taiwan, we estimated the annual incidence of AMI-associated ED visits by Poisson regression models. We used segmented regression techniques to evaluate differences in the annual rates and in the year-to-year changes in AMI-associated ED visits between 2003 and 2012. Medical comorbidities such as diabetes mellitus, hyperlipidemia, and hypertensive disease were considered as potential confounders. Overall, the number of AMI-associated patient visits increased from 8130 visits in 2003 to 12, 695 visits in 2012 ( P -value for trend < 0.001), corresponding to an average annual growth rate of 5.3% (95%confidence interval [CI]: 0.5–10%). Although age was a major risk factor for AMI-associated ED visits, the statistical association was observed in middle-to-old (aged 40–64; P -value < 0.001) and older aged individuals (aged ≥65; P -value <0.001). As compared to 2003–2007, AMI-associated ED visits increased slightly during the intervention roll-in period (2007–2009, slope = 394.5, P -value = 0.117) followed by a dramatic uptake in the early post-intervention period (2010–2012, slope = 1037, P -value = 0.083). There was evidence suggesting for a significant intervention effect of the GRHAC program on identifying critically ill patients with AMI-associated diagnosis at the ED. As the program evaluation is still ongoing, we expect to observe a sustained program effect on hospitals' capacity for timely and correctly diagnosing and managing patients presenting with AMI-associated symptoms or signs at the ED.